- sanksi pidana penyalagunaan narkotika golongan 1 bukan tanaman untuk diri sendiri studi putusan 731/pid.sus/2021/pn jkt selatan: - - Muhammad Isa Nurwahyu; I komang suka'arsana (Fakultas Hukum Universitas Trisakti, 2023)
Drug abuse is when someone uses drugs not for medicinal purposes, but that person only wants to enjoy the effects of the ingredients of these drugs. The problem is: what are the criminal sanctions for drug abuse for oneself (study of decision number 731/pid.sus/jkt south)? and whether the criminal sanction imposed by the judge is in accordance with the purpose of punishment in the Narcotics Law (study of decision number 731/pid.sus/jkt Selatan)? This research is normative, The results of the research and the conclusion, that the defendant Anggi Affani alias Acil was caught red-handed with evidence of methamphetamine weighing 0.1724 grams. And subject to punishment in Article 112 paragraph (1) of the law on narcotics. So according to the author's analysis of Article 127 paragraph (3) it is very appropriate to be given to Anggi Affani alias acil Article 127 paragraph (3), in the case of the abuser as referred to in paragraph (1) the abuser is required to undergo medical rehabilitation and social rehabilitation. It is proved that the defendant Anggi Affani alias Acil is a narcotics abuser. Based on the Supreme Court circular letter No. 04 of 2010 evidence of methamphetamine below 1 gram meets the rehabilitation requirements.